Genome-Wide Association Mapping in Rice MAGIC indica panel detects QTLs and Genes for Broad-spectrum resistance breeding against African Bacterial Blight - Okello, Moses; Ssemakula, Mildred Ochwo; Lamo, Jimmy; Onaga, Geoffrey; Odong, Thomas L; Geoffrey, Tusiime; Tukamuhabwa, Phinehas; Mukasa, Settumba B; Peter, Wasswa; Ogwal, Jonathan; Oliva, Ricardo (ORYZA-An International Journal of Rice, 2024)
Rice (Oryza sativa) bacterial blight (BB) is a direct threat to production in Africa. The extent of damage on the continent is not known. We conducted a genome-wide association study (GWAS) to seek out Quantitative trait loci (QTL) that confer the broad-spectrum resistance (BSR) to rice Xanthomonas oryzae pv. oryzae in the rice Multiparent advanced generation intercross (MAGIC) population. The diverse genetic composition and high levels of recombination, are potential resources for the identification of QTL for BSR. Dealing with the ever-evolving Xoo requires identification of novel R gene and resistance quantitative trait loci (QTL). We conducted a genome-wide association study (GWAS) using 250 rice MAGIC indica panel to evaluate for resistance to three Xoo strains from Cote D'Ivoire, namely XooCIkor, XooCIgag and XooCIcii2 which are prevalent highly virulent pathotypes.Using the 3 K RG 4.8mio filtered SNP Dataset, a total of 3 QTL associated with BB resistance on chromosome 9, 6 and 5 were identified.The results of the GWAS identified novel loci that gives useful insight for more investigation and also validated known genes underlying resistance to virulent African strains of BB. Genetic donors identified in this will help plant breeders in improving and broadening resistance to BB.Key words: Africa, Bacterial blight (BB), broad-spectrum resistance (BSR), multiparent advanced generation intercross (MAGIC), Quantitative trait loci (QTL), Xanthomonas oryzae pv. oryzae